GENE SET ENRICHMENT ANALYSIS IN AMYOTROPHIC LATERAL SCLEROSIS. Issue 11 (14th October 2015) - Chen, Zhongbo; Lin, Kuang; Shatunov, Aleksey; Jones, Ashley; Al-Chalabi, Ammar
Abstract : Background: Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease. We examined the phylogenetics of ALS-susceptibility genes from our previously-published genome-wide association study (GWAS). Methods: We examined the association between ALS-susceptibility genes and hybridisation from the Neanderthal genome using a modified gene set enrichment analysis (GSEA). These gene sets comprise thirteen candidate regions for Neanderthal to non-African human gene flow [UCSC Genome Browser]. We ranked the ascending p-values of 442, 057 GWAS SNPs and simulated the distribution 100, 000 times. The resulting empirical p-value, comparing observed with expected mean rank, identified which gene sets are over-represented at the top of the rank list. Bonferroni corrections for multiple testing were applied. Results: 6, 402 imputed GWAS SNPs fell into the thirteen gene sets. We found that the regions on chromosomes 6 and 9 accrued the lowest observed mean ranks (8, 594 and 7, 096 respectively) and were not different from expected mean ranks after simulation for those regions – empirical p-values before Bonferroni correction were 0.086 for chromosome 6 and 0.071 for chromosome 9. Discussion: Using GSEA to evaluate European ALS GWAS data in the context of pre-defined gene sets refutes the theory that ALS-susceptibility loci may have arisen from Neanderthal to non-African modern human gene flow.